Xenograft of bio-3D printed scaffold-free cartilage constructs derived from human iPSCs to regenerate articular cartilage in immunodeficient pigs - Toshihiro Nonaka; Anna Nakamura; Daiki Murata; Hiromu Yoshizato; Shohei Kashimoto; Yukiko Nagaishi; Manabu Itoh; Denise Zujur; Chengzhu Zhao; Yoshiko Inada; Makoto Ikeya; Junya Toguchida; et al. (Regenerative Therapy)
Arthroplasty is currently the only option for reconstruction of large articular cartilage defects, mainly due to osteoarthritis. However, reconstruction with artificial materials has several issues such as deterioration, foreign body reaction, and bacterial infection. This study established a new method for articular cartilage reconstruction that fundamentally solves the problems associated with artificial materials by creating scaffold-free cartilage constructs and implanting them into extensive osteochondral defects without artificial materials. Tubular cartilage constructs were fabricated using a completely scaffold-free Kenzan bio-three-dimensional printing method with chondrogenic spheroids generated from human induced pluripotent stem cell-derived mesenchymal stem/stromal cells (iPSC-MSCs). The constructs were partially cut open to form a patch and implanted into osteochondral defects in the femoral trochlear groove of immunodeficient miniature pigs. The cartilage constructs were elastic and easy to handle, and abundant glycosaminoglycans and collagens were observed in the grafted site after implantation, as well as in the articular cartilage. Cells at this site were positive for human vimentin, indicating that the cartilage constructs were successfully engrafted into the host subchondral bone. Scaffold-free human iPSC-MSC-derived cartilage constructs implanted into osteochondral defects contribute to the regeneration of extensive osteochondral defects in the absence of artificial materials.